Neonatal overfeeding alters the functioning of the mesolimbic dopaminergic circuitry involving changes in DNA methylation and effects on feeding behavior. - Schumacher, Rocio (2023)
Mesolimbic dopaminergic circuit is essential for food reward and motivational behaviors and can contribute to weight gain and obesity. Litter reduction is a classical model for studying the effects of neonatal overfeeding and overweight. Litters of Wistar rats were reduced to 4 pups/dam for small litter (SL) and 10 pups/dam for normal litter at postnatal day (PND) 4. Immediately after performing the feeding behavior tests, the animals were sacrificed in PND21 and PND90. The ventral tegmental area (VTA), Nucleus Accumbens Core (NAcC) and Shell (NAcSh) were isolated from frozen brain sections using the Palkovits micropunch technique. RNA and DNA were extracted from these areas, gene expression was measured by RT-qPCR and DNA methylation levels were measured by MSRM-qPCR technique. SL-PND21 animals presented increased expression levels of Tyrosine Hydroxylase and Dopamine Receptor D2 in VTA, decreased expression levels of dopamine active transporter (DAT) in VTA, and higher expression levels of DAT in NAcC. On the other hand, SL-PND90 animals showed decreased expression levels of Dopamine Receptor D1 and higher expression of DAT in NAcSh. These animals also evidenced impaired sensory-specific satiety. In addition, altered promoter methylation was observed at weaning, and remained in adulthood. This work demonstrates that neonatal overfeeding induces disruptions in the mesolimbic dopaminergic circuitry and causes alterations in feeding behavior from weaning to adulthood, suggesting that the neonatal period is critical for the normal development of dopaminergic circuit that impact on feeding behavior.